Disclosure of the total novel in Conversation in The Cathedral: Artificians and falsifications - Novoa Castillo, Pedro Félix (2020)
The present research work is about the representation of the total novel in Conversation in the Cathedral of Mario Vargas Llosa through the notions of oppositions and brittle realities. For this, the category of “broken glass” is proposed to understand a little better the fact that the destruction of cultural schemes is done by way of partitioning more or less visible pieces. And that no matter how much they configure a new aesthetic and that it has exploded in the very center of its axis, there are pieces of climatic moments of art history, permanent and in force in any new aesthetic. From this conception, the study will address the use made by Vargas Llosa of Realism, American & European literature, cinema, among others. Also, in this reconstruction of a totality, it will be observed that it is actually apparent, since it will be essentially split. Despite this, the contribution and narrative virtuosity that the author bequeathed in the notable years of Latin American Boom will be valued.